Good-bye to Homer Martin - Benedict, Daniel (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1992)
People frequently overdo the parallels between events and institutions in Canada and the United States, even confusing them at times. The 1939 split in the United Auto Workers Union was a case in point. The end of the 1930s was a period of stresses and strains for the unions in both countries. For the UAW, relations with the employers went on side by side with a struggle between Socialists, Communists, anti-Communists and their respective allies. Though divided, Socialists and Communists at times took the same side. One such time was in 1938-39. The high point of the period was when both joined in getting rid of the "International President," Homer Martin. In Canada, the two principal factions carried on a bitter struggle for the leadership of the union, slowing down only a bit while they both lined up with the opposition to Martin in the US. In the process, the first Canadian director of UAW, the Socialist Charles Millard, also lost his post. In the US, meanwhile, the two main factions concentrated on defeating Martin, while jockeying for position for their future struggle for the leadership.